2007
DOI: 10.1209/0295-5075/77/50004
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic resonance with weak monochromatic driving: Gains above unity induced by high-frequency signals

Abstract: Abstract. -We study the effects of a high-frequency (HF) signal on the response of a noisy bistable system to a low-frequency subthreshold sinusoidal signal. We show that, by conveniently choosing the ratio of the amplitude of the HF signal to its frequency, stochastic resonance gains greater than unity can be measured at the low-frequency value. Thus, the addition of the HF signal can entail an improvement in the detection of weak monochromatic signals. The results are explained in terms of an effective model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 16 publications
(34 reference statements)
1
2
0
Order By: Relevance
“…Those findings indicated that the arrays were indeed operating in nonlinear regimes. Similar results have been reported for single bistable units driven by a suprathreshold sinusoidal force [12], by subthreshold multi-frequency forces [13,14,15,16,17,18], or by a subthreshold sinusoidal force in the presence of a strong, high-frequency monochromatic signal [19]. Nevertheless, to the best of our knowledge, gains larger than unity have never been observed when the single bistable unit is driven by just a subthreshold sinusoidal force.…”
Section: Introductionsupporting
confidence: 89%
“…Those findings indicated that the arrays were indeed operating in nonlinear regimes. Similar results have been reported for single bistable units driven by a suprathreshold sinusoidal force [12], by subthreshold multi-frequency forces [13,14,15,16,17,18], or by a subthreshold sinusoidal force in the presence of a strong, high-frequency monochromatic signal [19]. Nevertheless, to the best of our knowledge, gains larger than unity have never been observed when the single bistable unit is driven by just a subthreshold sinusoidal force.…”
Section: Introductionsupporting
confidence: 89%
“…The potential is renormalized, with its amplitude controlled by the strength and frequency of the HF field. The mechanism underlying the potential renormalization is the so-called vibrational resonance, intially introduced [3] and observed [4][5][6][7] in bistable systems. Our experiment uses cold atoms in a dissipative optical lattice as a model system.…”
Section: Potential Renormalization By High-frequency Drivingmentioning
confidence: 99%
“…This situation resembles the effect of a high-frequency signal in an isolated bistable system. In the later case, the high-frequency signal can be removed from the description by means of an effective bistable potential with modified parameters, with the consequence that previously subthreshold driving amplitudes can become suprathreshold from the point of view of the effective potential [14]. In contrast, the effective dynamics induced by the high-frequency signal has been shown to provoke the opposite effect on an excitable system, being able to suppress the excitable character of the system [15].…”
Section: Discussionmentioning
confidence: 99%